Safety Profile, Toxicokinetic, and Intestinal Absorption Differences of a Naturally-Derived Anti-Rheumatic Drug, Sinomenine Hydrochloride, in Normal and Arthritic Rats - Yini He; Hong Huang; Gejing Li; Ye Zhang; Junjie He; Ye Lin; Feichi Wu; Jianye Yan; Xiong Cai; Liang Liu (Pharmaceutics)
Background/Objective: Sinomenine hydrochloride (SH), a natural anti–rheumatic drug derived from the Chinese medicinal plant Sinomenium acutum, demonstrates disease–modifying properties but lacks comprehensive safety and toxicokinetic (TK) comparisons between physiological and pathological states. This study evaluated SH’s safety profile, TK parameters, and intestinal absorption differences in adjuvant–induced arthritis (AIA) and normal rats. Methods: Safety assessments determined median lethal doses (LD50) in female Sprague Dawley rats. TK parameters were analyzed via a validated ultrahigh performance liquid chromatography-tandem mass spectrometry approach after single oral administration of 600 mg/kg SH. Plasma protein binding (PPB) were measured using equilibrium dialysis. Intestinal absorption was evaluated through everted gut sac experiments, with P–glycoprotein (P–gp) inhibition tested via verapamil co–administration. Results: LD50 values revealed AIA rats tolerated SH better than normal rats (1179 vs. 805 mg/kg). TK analysis showed that Cmax, AUC(0-t), and AUC(0-∞) of SIN in normal rats were 2.01, 1.94, and 2.14 times higher than in AIA rats, respectively, while CL/F and V/F in AIA rats were 2.24 times greater. In addition, the PPB of SIN in normal rats was 2 times greater than that in AIA rats. AIA rats exhibited significantly lower SH absorption in the jejunum and ileum compared to normal rats. Notably, verapamil co–administration markedly increased SH absorption across most intestinal segments. Conclusions: Pathological states significantly alter SH’s safety and TK profiles. Enhanced tolerance in AIA rats correlates with reduced intestinal absorption via altered P–gp activity and decreased PPB. These findings emphasize the necessity of disease–specific evaluations for optimizing SH’s therapeutic safety in pathological contexts.